7.1% efficient co-electroplated Cu2ZnSnS4 thin film solar cells with sputtered CdS buffer layers. Issue 2 (18th September 2015) - Tao, Jiahua; Liu, Junfeng; Chen, Leilei; Cao, Huiyi; Meng, Xiankuan; Zhang, Yingbin; Zhang, Chuanjun; Sun, Lin; Yang, Pingxiong; Chu, Junhao
Abstract : Cu2 ZnSnS4 (CZTS) thin films with fine control over composition and pure phase were fabricated by sulfurization of co-electroplated Cu–Zn–Sn–S precursors. Abstract : Cu2 ZnSnS4 (CZTS) thin films with fine control over composition and pure phase were fabricated by sulfurization of co-electroplated Cu–Zn–Sn–S precursors. We have systematically investigated that the concentration of Cu(ii ) ions can influence the properties of CZTS absorber layers and the photovoltaic performance of the resulting solar cell devices. The results indicate that an increase in Cu(ii ) concentration almost linearly increases the Cu content in the final CZTS thin films, greatly enhances the (112) preferred orientation, significantly improves the crystallinity of the absorber layer, remarkably reduces the ZnS secondary phase, and hence improves their photovoltaic performance. However, a further increase in the Cu(ii ) concentration degrades the crystal quality of the absorber layer, and forms the CuS x secondary phase, which is quite detrimental to the device photovoltaic performance. Here we introduce a novel sputtered CdS buffer layer for the CZTS solar cells. For the first time, co-electrodeposited CZTS solar cells exceed the 7% efficiency threshold. These findings offer new research directions for solving persistent challenges of chemical bath deposition of CdS in CZTS solar cells.